2019
DOI: 10.1108/ijppm-05-2018-0182
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, job satisfaction and performance links in private education institutes of Pakistan

Abstract: Purpose The purpose of this paper is to get an insight into which form leadership either transactional leadership (TAL) or transformational leadership (TFL) is most effective in the educational sector of Pakistan and to determine the impact of each on the employee job satisfaction (EJS) and employee job performance (EJP). Given research site observation, appropriate leadership was essential to high-quality education in Pakistan. Design/methodology/approach Data are collected through a survey based on e-mail/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
115
1
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 34 publications
18
115
1
16
Order By: Relevance
“…This means that increased job satisfaction leads to improved employee performance. The results of this study are in line with the results of (Bakotić, 2016;Kampkötter,2017;Platis et al, 2015;Torlak & Kuzey, 2019;Yuen et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This means that increased job satisfaction leads to improved employee performance. The results of this study are in line with the results of (Bakotić, 2016;Kampkötter,2017;Platis et al, 2015;Torlak & Kuzey, 2019;Yuen et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the amount of workrelated stress and reward attractiveness are key determinants of job satisfaction. Torlak and Kuzey (2019) found that inspirational management, intellectual stimulation, and personal attention were positively associated with job satisfaction and job performance. Whereas, the possible rewards related to job satisfaction and job performance had no significant effect.…”
Section: Employee Performancementioning
confidence: 95%
“…This result has been considered that the hypothesis (H3 and H3) is rejected. Temuan ini mendukung temuan hasil penelitian yang dilaksanakan oleh Torlak & Kuzey (2019). This finding supports the findings of the research conducted by Torlak & Kuzey (2019).…”
Section: Figuresupporting
confidence: 86%
“…Job satisfaction is referred to as the level or extent of contentment employees feel with the workplace and the work they do (Torlak & Kuzey, 2019;Kreitner & Kinicki, 2013). Similarly, employee's job satisfaction is based on individual feeling or perception of satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Others leave as a result of low level of job satisfaction from previous places of work, while many may not really be satisfied with their jobs. This perturbing development demands a holistic approach, even as studies have shown that leadership plays a critical role in ensuring that organizations achieve sustainable growth (Torlak & Kuzey, 2019). More so, the high rate of migration poses a negative effect on the active population of the country and further decreases the performance of organizations (formal or informal) in Nigeria (Omonijo, Nnedum & Ezeokana, 2011); hence the need to examine the relationship between workplace leadership and job satisfaction and how it affect sustainable productivity in Nigeria.…”
Section: Introductionmentioning
confidence: 99%